A Study on the Internet Attention of Non-heritage Tourism Performing Arts Products Based on Baidu Index --- Taking “Seeing Pingyao Again” as an Example - Lv, Mengqi (International Journal of Global Economics and Management, 2024)
Cultural performing arts is an important manifestation of regional tourism development, and in the era of big data, analyzing the network attention of non-heritage cultural tourism performing arts products helps the dissemination of non-heritage culture and the healthy development of non-heritage tourism. Based on the Jitterbug Index platform, the user search index of Seeing Pingyao Again from January 2014 to December 2023 was retrieved, and the characteristics and trends of the overall search index, the PC search index and the mobile search index were analyzed, which in turn led to the proposal of relevant suggestions for the development of cultural tourism performing arts products.